The answer is 15 cookies and 5 brownies
Answer:
Step-by-step explanation:
interchange x and y
y= 1/(x - 2)
x = 1 / (y - 2) Multiply both sides by y - 2
x(y - 2) = 1 Remove the brackets
xy - 2x = 1 Add x to both sides
xy = 1 + 2x Divide by x
y = (1 + 2x)/x
The brackets have been destroyed. The answer is as I've given it.
y = (1/x) + 2
Answer:
x = t(a+p)/4
Step-by-step explanation
Given the expression
a=4x/t - p
We are to make x the subject of the formula
a=4x/t - p
Add p to both sides
a+p = 4x/t - p+p
a+p = 4x/t
Cross multiply
t(a+p) = 4x
Rearrange
4x = t(a+p)
Divide both sides by 4
4x/4 = t(a+p)/4
x = t(a+p)/4
10 divided by 2 =5 because it ends at 10 and goes back by 2 and there are 5 loops